STRATEGI SATLANTAS POLRES KOTA SALATIGA DALAM MEWUJUDKAN PELAYANAN PRIMA (STUDI PENELITIAN PADA PELAYANAN PENERBITAN SIM BARU) - Hieronymus Kakaputra Waluyo; Nunik Retno Herawati (Journal of Politic and Government Studies, 2026)
The service for issuing new Driving Licenses (SIM) at the Driver License Administration Unit (Satpas) of the Traffic Police Unit (Satlantas) of the Salatiga City Police Department still faces various challenges, as indicated by fluctuations in Community Satisfaction Survey (SKM) scores throughout 2024, as well as public complaints regarding service speed, queue clarity, and information on medical and psychological examination fees. This study aims to analyze the strategy of the Traffic Police Unit of the Salatiga City Police Department in realizing excellent service in the issuance of new Driving Licenses (SIM). This research employed a descriptive qualitative method, with data collected through interviews, observations, and documentation. The analysis was conducted using Osborne and Plastrik’s Five Strategies Theory, which consists of core strategy, consequences strategy, customer strategy, control strategy, and culture strategy, while service quality was measured using the nine elements of the Community Satisfaction Survey (SKM) based on the Regulation of the Minister of Administrative and Bureaucratic Reform (PermenPANRB) Number 14 of 2017. The results indicate that the service strategies implemented are fairly comprehensive and have been carried out quite effectively through the hierarchical internalization of vision and mission, the implementation of reward and punishment systems, the provision of complaint channels, the development of service innovations such as Saturday service, afternoon driving test training programs, facilities for vulnerable groups and persons with disabilities, multi-layered supervision of service processes, and the establishment of a work culture oriented toward excellent service. The implementation of these strategies has supported the ease of requirements, clarity of procedures, timeliness of service delivery, staff competence, fee transparency, as well as the availability of adequate facilities and infrastructure. Nevertheless, several challenges remain, including suboptimal coordination with external partners responsible for medical and psychological examinations, insufficient dissemination of complaint procedures to the public, and the need to expand supervision to prevent potential misconduct outside the Satpas area. Therefore, improved coordination, strengthened supervision, and optimized dissemination of service information are necessary to achieve excellent service in the issuance of new Driving Licenses (SIM).